SUMY ALGEBRAICZNE :)
1) (x+4)+(2x-6)= ?
2) -(2y+3x)+(-4y+2x+1) = ?
3) -(x-2x)-(4x+xy) = ?
4) 4(2x-3)-2(3x+1) =?
5) -6(2x-3)-2(3x+1) =?
6) (x+7)(2x-1) = ?
7) 3+15-5= ?
8)-7+11-6 = ?
9)5-(-12)-7+14= ?
10) -2-(8)-6-3= ?


BARDZO PROSZĘ ROZWIĄŻCIE MI TO :) OCZYWIŚCIE NAJLEPSZE BĘDZIE.

3

Odpowiedzi

2010-03-22T20:33:16+01:00
1) (x+4)+(2x-6)= 3x - 2
2) -(2y+3x)+(-4y+2x+1) = -2y-3x-4y+2x+1= -6y-x+1
3) -(x-2x)-(4x+xy) = -x+2x-4x-xy=-3x-xy
4) 4(2x-3)-2(3x+1) =8x-12-6x-2=2x-14
5) -6(2x-3)-2(3x+1) =-12x+18-6x-2=-18x+16
3 2 3
2010-03-22T20:43:35+01:00
1) (x+4)+(2x-6)= x+4+2x+6 = 3x+10
2) -(2y+3x)+(-4y+2x+1) = -2y-3x-4y+2x+1= -6y-x+1
3) -(x-2x)-(4x+xy) = -x+2x-4x-xy= -3x-xy
4) 4(2x-3)-2(3x+1) =8x-12 -(6x-1) = 8x-12-6x+1 = 2x-11
5) -6(2x-3)-2(3x+1) =-12x+18-(-6x-1) = 12x+18+6x+1= 18x+19
6) (x+7)(2x-1) =2xkwadrat -x+14x-7 = 2xkwadrat +13x-7
7) 3+15-5= 13
8)-7+11-6 = -2
9)5-(-12)-7+14= 24
10) -2-(8)-6-3= -19
1 1 1
  • Użytkownik Zadane
2010-03-22T21:11:34+01:00
1) (x+4)+(2x-6)= 3x-2
2) -(2y+3x)+(-4y+2x+1) = -6y+x+1
3) -(x-2x)-(4x+xy) = -3x+xy
4) 4(2x-3)-2(3x+1) = (8x-12)-(6x+2) = 2x-14
5) -6(2x-3)-2(3x+1) = (-12x+18)-(6x+2) = -18x + 16
6) (x+7)(2x-1) = 2x²+14x-x-7=2x²+13x-7
7) 3+15-5= 13
8)-7+11-6 = -2
9)5-(-12)-7+14= 24
10) -2-(8)-6-3= -19